2018
DOI: 10.1093/mnras/sty3086
|View full text |Cite
|
Sign up to set email alerts
|

Onset of non-linear internal gravity waves in intermediate-mass stars

Abstract: Internal gravity waves (IGW) propagate in the radiation zones of all stars. During propagation, their amplitudes are affected by two main features: radiative diffusion and density stratification. We have studied the implications of these two features on waves traveling within the radiative zones of non-rotating stars with stellar parameters obtained from the one dimensional stellar evolution code, MESA. As a simple measure of induced wave dynamics, we define a criterion to see if waves can become nonlinear and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
(92 reference statements)
4
23
0
Order By: Relevance
“…A narrow range around 10 µHz is apparent where the nonlinearity is highest. We note that this looks very similar to Spectrum K and Spectrum LD in figure 5 of Ratnasingam et al (2019) for convective velocity boosted by a factor of three with respect to the stellar models. The strongest nonlinearity in Fig.…”
Section: Nonlinearity Parametersupporting
confidence: 78%
See 2 more Smart Citations
“…A narrow range around 10 µHz is apparent where the nonlinearity is highest. We note that this looks very similar to Spectrum K and Spectrum LD in figure 5 of Ratnasingam et al (2019) for convective velocity boosted by a factor of three with respect to the stellar models. The strongest nonlinearity in Fig.…”
Section: Nonlinearity Parametersupporting
confidence: 78%
“…From linear theory, one expects the amplification of IGW toward the surface due to density stratification. As shown in Ratnasingam et al (2019) for spherical geometry, the prediction for IGW amplification is given by (in the notation 2 of EM19)…”
Section: Wave-amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the 3D simulations of solarlike stars by Alvan, Brun, and Mathis (2014) and Alvan et al (2015) and of intermediate-mass stars by Edelmann et al (2019) and showed clear modal structure of internal g modes, it remains unclear if and which of the internal waves become resonant modes. This depends on the profile of the wave's eigenfunction, on its propagation and dissipation properties, on the efficiency of the radiative damping, and on the onset of nonlinearity (Ratnasingam, Edelmann, and Rogers, 2019). A snapshot of the temperature variations accompanying the driving of IGWs and their propagation from the 3D hydrodynamical simulations by Edelmann et al (2019) is shown in Fig.…”
Section: Convectively Driven Internal Gravity Wavesmentioning
confidence: 99%
“…They suffer from linear damping due to radiative diffusion (Press, 1981;Garcia Lopez and Spruit, 1991;Zahn et al, 1997). The low-frequency, short-wavelength waves are damped strongly and behave like traveling waves (Ratnasingam et al, 2019). Higherfrequency waves can be reflected at the outer turning points and interfere constructively to form global normal modes (Prat et al, 2016).…”
Section: Tidally Excited Oscillations (Teos) In Heartbeat Starsmentioning
confidence: 99%